ANALISIS YANG MEMPENGARUHI KEPATUHAN MINUM OBAT HIPERTENSI PADA LANSIA DI PUSKESMAS PADONGKO KABUPATEN BARRU - Rosdiana Said Rosdiana Said (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Hypertension or high blood pressure is one of the risk factors for cardiovascular disease with a fairly high prevalence and mortality, especially in developed countries and developing countries, including Indonesia. Hypertension is caused by high blood pressure that exceeds normal. Currently, hypertension is still a major health problem. To analyze the factors affecting drug adherence to the elderly at padongko health center, barru regency in 2021. The type of research is analytic observational research with a cross sectional research design, sample in the study as many as 73 respondents with Random Sampling technique, simple random retrieval. The results showed that there was no influence between knowledge on medication adherence in the elderly (p = 0.626) > (0.05), there was no influence between attitudes towards medication adherence in the elderly, with p value (p = 0.532) > (0, 05) , There is no effect of length of treatment on adherence to medication in the elderly, with a value of p = 0.915 > 0.05, There is no effect of access to services on adherence to taking medication in the elderly, with a value of (p = 0.713) > (0.05) , There is an influence between family support on medication adherence in the elderly, with a p value = 0.047 > 0.05, There is an influence between the role of health workers on medication adherence in the elderly, with a p value = 0.026 > 0.05. Suggestion: Improving better services, especially in providing information services on the use of drugs to the elderly so that patients understand and can obey in consuming hypertension drugs.